Cyberbullying and Digital Citizenship: The Effectiveness of Tech-Integrated Prevention Programs - Muhamad Habib; Rami Hariri; Yara Abed (Journal Emerging Technologies in Education, 2026)
Background. Cyberbullying has become a persistent issue in digitally mediated educational environments, posing serious risks to students’ psychological well-being, academic engagement, and social interaction. As digital technologies are increasingly embedded in learning processes, conventional punitive approaches to cyberbullying prevention are insufficient. This condition underscores the need for preventive strategies that emphasize ethical participation, responsible online behavior, and the cultivation of digital citizenship through pedagogically grounded technology integration. Purpose. This study aimed to examine the effectiveness of technology-integrated prevention programs in reducing cyberbullying behaviors while simultaneously enhancing students’ digital citizenship competencies, particularly in terms of ethical awareness, responsible online conduct, and proactive engagement in online communities. Method. A mixed-methods research design was employed, combining a quasi-experimental approach with qualitative inquiry. Quantitative data were collected through pre- and post-intervention surveys measuring levels of cyberbullying perpetration, victimization, and digital citizenship awareness. Qualitative data were obtained through semi-structured interviews, focus group discussions, and reflective digital learning activities to capture students’ perceptions, attitudes, and behavioral changes following the intervention. Results. The findings demonstrate a significant reduction in both cyberbullying perpetration and victimization after the implementation of the tech-integrated prevention program. In addition, students showed notable improvements in responsible online behavior, ethical awareness, and learning engagement. Qualitative evidence further revealed positive shifts in empathy, moral reasoning, and students’ willingness to intervene when encountering harmful online behavior. Conclusion. The study concludes that technology-integrated prevention programs are effective when digital tools are deliberately aligned with digital citizenship principles and ethical education. Integrating interactive digital learning with values-based instruction provides a sustainable and pedagogically sound approach to addressing cyberbullying in contemporary educational settings.